Development Of Educaplay-Based Educational Game Media in Ipas Subject On Energy Around Us for Grade 3 SDN Bulang 1 - Fitri Yuliatin; Didit Yulian Kasdriyanto; Faridahtul Jannah (International Journal of Educational Evaluation and Policy Analysis, 2026)
This study aims to develop an Educaplay-based educational game for the Natural and Social Sciences (IPAS) subject specifically the topic of "energy around us" for third-grade students at SDN Bulang 1, and to determine the validity, practicality, and effectiveness of the developed media. The study was motivated by low student learning outcomes, a lack of instructional media usage, and a teaching process that remained teacher-centered. The research employed the Research and Development (R&D) method using the ADDIE model, which comprises five stages: Analysis, Design, Development, Implementation, and Evaluation. Data collection instruments included expert validation sheets, practicality questionnaires, and learning outcome tests. The results indicate that the developed Educaplay-based educational game achieved a very high level of validity, with validation scores of 92% from the subject matter expert and 95% from the media expert. The media's practicality was also rated very highly, with a 100% score from the class teacher and a 94.8% positive response from students. Furthermore, effectiveness testing showed an improvement in student learning outcomes; the average pretest score rose from 61.12 to 90.54 in the posttest, yielding an N-Gain score of 0.76, which falls into the high category. Based on these results, the Educaplay-based educational game is deemed highly valid, highly practical, and effective for use in third-grade IPAS instruction on the topic of energy around us.